Proceedings of the Forty-Eighth Annual ACM Symposium on Theory of Computing 2016
DOI: 10.1145/2897518.2897657
|View full text |Cite
|
Sign up to set email alerts
|

Textbook non-malleable commitments

Abstract: We present a new non-malleable commitment protocol. Our protocol has the following features:• The protocol has only three rounds of interaction. Pass (TCC 2013) showed an impossibility result for a two-round non-malleable commitment scheme w.r.t. a black-box reduction to any "standard" intractability reduction. Thus, this resolves the round complexity of non-malleable commitment at least w.r.t. black-box security reductions. Our construction is secure as per the standard notion of nonmalleability w.r.t. commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…opening). Recently Goyal et al [35] showed how to construct 3-round non-malleable commitments from standard assumptions when the adversary plays left and right sessions in parallel. Their scheme crucially relies on the power of split-state non-malleable codes.…”
Section: Additional Related Workmentioning
confidence: 99%
“…opening). Recently Goyal et al [35] showed how to construct 3-round non-malleable commitments from standard assumptions when the adversary plays left and right sessions in parallel. Their scheme crucially relies on the power of split-state non-malleable codes.…”
Section: Additional Related Workmentioning
confidence: 99%
“…We run Π OR in parallel with a 4-round public-coin one-one honest-extractable synchronous non-malleable commitment scheme Π nm 6 . A construction for such a scheme in 4 rounds was given by [GPR16]. The prover of the NMZK argument runs Π OR in order to prove either the validity of some N P-statement, or that the non-malleable commitment computed using Π nm contains a trapdoor.…”
Section: Technical Overview On Our Nmzkmentioning
confidence: 99%
“…Indeed if the sender of NM could decide the message to commit in the last round, then Sim NMZK can simply compute the first round of NM, extract the signature, and compute the last round of NM by committing to σ 1 ||σ 2 . It is important to observe that even though the non-malleable commitment scheme of [GPR16] fixes the message to be committed in the third round, there is in general no guarantee that such a scheme is secure against an adversary that adaptively chooses the challenge messages in the last round of the non-malleability security game. Therefore, even though the completeness of our scheme would work without using the trick of [COSV16], it would be unclear, in general, how to prove the security of our final scheme.…”
Section: For More Details)mentioning
confidence: 99%
See 2 more Smart Citations